Evaluating The Effectiveness And Applicability Of Iso 21001:2018 For Quality Assurance In Higher Education - Tanti Ardianti; Irham Ramdani (International Journal of Management, Innovation, and Education, 2024)
This study critically evaluates the effectiveness and applicability of the ISO 21001:2018 standard as a framework for quality assurance in higher education institutions. The research aims to examine how the standard’s principles such as organizational context, leadership, stakeholder engagement, and continual improvement are implemented and adapted to the unique characteristics of higher education. Using a qualitative descriptive approach, the study analyzes empirical findings from institutional documentation, interviews with quality managers, and secondary literature related to educational management systems. Results reveal that ISO 21001:2018 provides a structured and globally recognized model for enhancing educational quality through data-driven decision-making, risk-based thinking, and stakeholder-centered management. However, its full applicability is challenged by contextual factors such as institutional autonomy, cultural diversity, and resource disparities across universities. Despite these limitations, the study concludes that ISO 21001:2018 remains a valuable tool for promoting transparency, accountability, and continuous improvement within academic institutions, provided that its implementation is contextualized to align with higher education governance and learning outcomes.